Evaluating the performance of a web-based vehicle blind zone estimation application: Validation and policy implications - Drake, Juwon; Vennema, Alessandra; Slonim, Lily; Englin, Eric; Brodeur, Alyssa; Epstein, Alexander K.; Fisher, Donald L. (Frontiers in Future Transportation, 2023)
Pedestrian fatalities have been increasing in the United States over the past decade; in 2021 they reached a 40-year high and together with an increasing number of bicyclist fatalities surged to over 8,400 vulnerable road users (VRUs) killed by motor vehicle crashes. There is widespread recognition of the link between passenger fleets transitioning from sedans to SUVs and pick-up trucks and the increase in vulnerable road user fatalities. Larger light-duty vehicles generally have larger blind zones, and larger blind zones are prominently linked to crashes with vulnerable road users. Heavy-duty commercial trucks, which comprise only four percent of vehicles on the road, are disproportionally associated with over eight percent of vulnerable road user deaths. With direct vision unregulated in the United States, there is a limited domestic market for large trucks with high direct vision despite research showing that one-quarter of the approximately 620 annual truck-involved pedestrian and bicyclist fatalities result from low-speed maneuvers with impaired direct vision and could be prevented by higher vision truck cabs. Communicating the seriousness of this problem is critical. This methods article presents an easy-to-use tool designed to give the public and fleet managers information to assess vehicle safety by quantifying driver blind zones using whatever driver eye positions are thought to be most applicable and with the option to standardize said eye position. Previously, measures of the percentage of volume surrounding the vehicle that cannot be seen or the number of people outside the vehicle that can fit in the blind zone could only be made with specialized instrumentation. The web-based application described, VIEW or visibility in elevated wide vehicles, can be used by anyone with a camera and access to the internet to obtain within approximately 15 min a reasonably accurate measure of the blind zone size, considerably faster than manual measurement methods. This article details the app usage procedure as well as the validation work conducted. In summary, the safety culture around SUVs, pickup trucks, and heavy-duty commercial trucks may change if drivers had an easy-to-use method to determine how much situational awareness they would be missing before they purchased a particular vehicle.